Strategi Belajar Structure Mahasiswa Program Studi Pendidikan Bahasa Inggris Universitas Palangka Raya (UNPAR) - Ranti, Apni (Jurnal Studi Agama dan Masyarakat, 2010)
This study was aimed at: 1) describing the studentsâ âStructureâ learning strategies, 2) revealing the factors that stimulate the students to apply certain learning strategies, 3) categorizing strategies supported the students to achieve satisfied score, 4) learning obstacles faced by the students.This research was a naturalistic descriptive. The subjects of the research were students of the English Education Study Program of Palangka Raya University who attended âStructureâ IV class established by using snowball sampling. Data were collected through observation, in-depth interview, and documentation. The data were analyzed using the techniques proposed by Miles and Huberman, which included data collection, data reduction, data display, and verification.The results of the study show that the English Education Study Program students ofPalangkaRayaUniversityapply 6 learning strategies. They are cognitive (repeating the lesson, doing the exercises, making notes, highlighting, making summaries, comprehending, remembering, using prior knowledge, and translating), metacognitive (focusing on attention, linking the information, and preparing before class), memory (making sentence patterns), social (asking questions and discussing), compensation (guessing, switching first language (L1) to target language (TL), looking for other references, and using the dictionary), and affective (using relaxation and breathing deeply). The factors that stimulate students to use certain learning strategies are divided into two kinds, namely internal and external factors. Internal factors include attitude, motivation, concentration, intelligence, and habits. External factors include study material, environment, and the lecturer. The most supporting learning strategies in gaining satisfactory scores are cognitive, metacognitive, and memory strategies by doing the exercises, rereading the material, paraphrasing the material, comprehending the material, focusing on attention, and memorizing.